Desenvolvimento neuropsicomotor aos 4 e aos 8 meses de idade corrigida de crianças nascidas prematuras - Caroline de Oliveira Alves (2012)
Gestational age and birth weight are risk factors for child development, and the preterm small for gestational age may have more chance of neurological morbidity. In this study we investigated the psychomotor development using Bayley III Test on preterm infants less than 34 weeks gestational age. The children were assessed by Bayley III cognitive, language and motor scoring scales at four and eight months of corrected gestational age. 105 children were evaluated at four month; at eighth month fourteen children did not attend for reassessment. 47.3% of the analyzed sample were male, 76.9% were born under thirty weeks of gestation age and 67.0% received antenatal steroids. The birth weight and bronchodysplasia were related to the continued stateof developmental delay, while intervention after referral was related to improvement in the overall development of preterm infants.When the sample was classified as small and appropriate for gestational age, there were significant differences in development between the groups. Small for gestational age children showed worse results in the language and motor scales when compared to the group of appropriated for gestational age. The study showed the importance of systematic monitoring of preterm infants born younger than 34 weeks. The bronchodysplasia and birth weight are related to worse development and systematic intervention as favoring the improvement in development.